Sterilization of the mentally handicapped - a comparative legal research between United Kingdom and Malaysia / Tuan Nursyazlin Nabila Tuan Abdullah, Nur Khairunnisa Liyana Mohd Yusoff and Zainal Narudin. - Tuan Abdullah, Tuan Nursyazlin Nabila; Mohd Yusoff, Nur Khairunnisa Liyana; Narudin, Zainal (Faculty of Law, 2008)
This research was conducted to highlight the vagueness of Malaysian law regarding sterilization especially on the mentally handicapped and to compare our law with that of the United Kingdom. We will also propose a solution to clarify the ambiguity in our law regarding this topic. Apart from that, the implied purpose of this research is to safeguard the mentally handicapped from the infringement of their rights. This topic was chosen because it had sparked our interest as it has never been brought up for discussion in Malaysia, while in the United Kingdom this topic had been quite a controversial subject. We hope that our research will shed some light as to clarify our laws with regards to the sterilization of the mentally handicapped people.